The Potential of Natural Ingredients Cardamom, Cloves, Black Pepper, and Ginger as Sources of Natural Antioxidant - Susana Elya Sudrajat; Diana Wijaya; Michelle Amanda Lau (Jurnal MedScientiae, 2023)
Antioxidants are well known for their various benefits in counteracting free radicals. However, artificial antioxidants are not recommended because of their toxic effects. Therefore, natural antioxidants are preferred and can be found in spices such as cardamom, cinnamon, clove, black pepper, and ginger which are the main ingredients of Pletok beer. This study was conducted to determine the best infusion method and the antioxidant potential of the five spices. This study used the infusion method at 90ºC and 100ºC, for 15 minutes and 30 minutes respectively, and the 2,2 diphenyl-1-picryhydrazyl (DPPH) method for antioxidant test. Then the dry weight of the sample was also measured on the 90ºC infusion method for 30 minutes. It is shown that ginger had the strongest antioxidant activity among all samples at the 100ºC extraction method for 30 minutes with an Inhibition Concentration 50 (IC50) value of 57.45 µg/mL. Then cinnamon with 67.55 µg/mL and black pepper with 80.57 µg/mL, both at 90ºC for 30 minutes. Cardamom was best at 90ºC for 15 minutes with 87.15 µg/mL. While cloves had the weakest antioxidant activity among all samples. The antioxidant activity of each ingredients is strongly determined by temperature and heating time.